2015
DOI: 10.1021/acs.jpcc.5b07465
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Work Function, and Silver Ad-Structures of High-Temperature Grown Ultrathin MgO Films on Ag(001)

Abstract: We characterized the high-temperature growth of ultrathin MgO films on Ag(001) at 783 K through analyzing the film's morphology and work function by noncontact atomic force microscopy (nc-AFM), scanning tunneling microscopy (STM), Kelvin probe force microscopy (KPFM) and assisting low-energy electron diffraction (LEED). At submonolayer coverage, one-atomic-plane-high MgO islands are formed, which are preferentially embedded into the silver surface and which are larger and more regular than the islands of those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…If we consider the reduced ceria film, we find a mean WF reduction of φ rCeria/Pt-Pt ≈ −0.60 ± 0.05 eV of the surface by the ceria film. We can only state that the ceria film follows the general trend of ultra-thin oxide films to modify the WF of the metal surface 61 : for instance, it has been shown that MgO ultra-thin films strongly reduce the WF of metal supports by more than 1 eV [61][62][63] , as indeed experimentally verified on MgO/Ag(001) 64,65 . In general, the basic mechanism behind is a net dipole formed at the film-support interface, which is a result of either a compressive electrostatic effect or of a net charge transfer between the film and the metal support 61 .…”
Section: Discussionmentioning
confidence: 96%
“…If we consider the reduced ceria film, we find a mean WF reduction of φ rCeria/Pt-Pt ≈ −0.60 ± 0.05 eV of the surface by the ceria film. We can only state that the ceria film follows the general trend of ultra-thin oxide films to modify the WF of the metal surface 61 : for instance, it has been shown that MgO ultra-thin films strongly reduce the WF of metal supports by more than 1 eV [61][62][63] , as indeed experimentally verified on MgO/Ag(001) 64,65 . In general, the basic mechanism behind is a net dipole formed at the film-support interface, which is a result of either a compressive electrostatic effect or of a net charge transfer between the film and the metal support 61 .…”
Section: Discussionmentioning
confidence: 96%
“…Crystal quality is checked using LEED and nc-AFM. Atomically flat silver terraces of 20 to 100 nm can be observed. , Two self-made effusion cells are used for Mg (549 K, 0.25 ML/min) and Pd (1418 K, 0.5 ML/min) evaporation. The growth of MgO thin films in the low-temperature growth mode is done by evaporating Mg inside the UHV chamber backfilled with 5 × 10 –8 mbar O 2 (>99.8% purity, Linde MINICAN, Munich, Germany) onto the Ag(100) substrate kept at 573 K. More details of MgO film growth and quality optimization are given elsewhere. , Pd is deposited onto the MgO film at 473 K with a nominal thickness ranging from 0.5 to 16 ML.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Here, is presented a systematic spectroscopic SFG study to (i) reveal the low-coverage adsorption kinetics of CO at Pd NPs with sizes ranging from 2.9 to 5.8 nm and with heights between three and nine atomic planes and (ii) to show that, in general, SFG can be used as an excellent experimental method to probe small quantities of adsorbed reactants at very small metal NPs with sizes in the few nanometer range. The Pd NPs are grown on MgO ultrathin films on Ag(100), which have proven to be suitable model substrates, , as also exemplified by the present work. , Furthermore, dipolar interaction modeling and assisting DFT calculations are involved to understand changes of dipolar, chemical, structural and electronic changes with NP size and their contribution to CO frequency changes. It is find that CO on the top (100) facets of large NPs (>4 nm) behaves very similarly to bulk Pd(100) whereas deviations become extremely significant when the NP diameter decreases below 3–4 nm.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a similar manner, giant hysteresis was observed for single-molecule magnets adsorbed on MgO/Ag(001) [15] Tailoring magnetic and catalytic properties and comparing experiments with theory require a precise control of the film growth and morphology down to the monolayer (ML) thickness and the realization of almost defect free layers. The electronic structure and morphology of ultrathin MgO films grown on Ag(001) under different conditions were studied by several groups using mainly XPS, STM or other scanning probe microscopy techniques [3,16,17,18,19,20]. Island formation was observed in a large temperature interval, spanning from 373 K to 673 K [21].…”
Section: Introductionmentioning
confidence: 99%